Long alkoxy substituted N2S2 porphyrins for liquid crystalline property. (14th February 2023) - Jana, Surajit
Abstract: Porphyrins with long alkoxy chains have assumed importance owing to their use as liquid crystalline materials. There are few reports on regular porphyrins with N4 core having long chains which exhibited liquid crystalline properties. Interestingly, to the best of our knowledge, there is only one report available with core‐modified porphyrins having N2 S2 core which showed the liquid crystalline properties. This contribution reports the synthesis of three new N2 S2 porphyrins having long octyloxy chains at the meso‐phenyls and the numbers of octyloxy groups were varied from 4 to 8 to 12 and their systematic study on liquid crystalline (LC) behavior. DSC studies indicate that only N2 S2 porphyrin having four octyloxy chains showed one LC transition (−18.25°C to 213.47°C) before melting into isotropic liquid (IL). The other two N2 S2 porphyrins, that is, porphyrins with 8 and 12 octyloxy chains did not show any LC transition. Abstract :